2013
DOI: 10.1080/09603123.2013.809702
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between blood lead levels and morbidities among workers employed in a factory manufacturing lead–acid storage battery

Abstract: The present study was carried out to find the relationship between blood lead levels (BLLs) and morbidities among 391 male workers employed in a factory manufacturing lead-acid storage batteries. A predesigned questionnaire was used to collect information on subjective health complaints and clinical observation made during a clinical examination. In addition to monitoring of BLL, other laboratory parameters investigated included hematological and urine-δ-aminolevulinic acid levels. Logistic regression method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[37] Kalahasthi et al . [24] reported that the odds ratio of BLLs was significantly associated with MSDs in workers from Pb-battery plant. In this study, the Pb-exposure in the form of elevated BLLs was significantly associated with workers who had MSDs at upper and lower back and ankle and foot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Kalahasthi et al . [24] reported that the odds ratio of BLLs was significantly associated with MSDs in workers from Pb-battery plant. In this study, the Pb-exposure in the form of elevated BLLs was significantly associated with workers who had MSDs at upper and lower back and ankle and foot.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the MSD morbidities among Pb-battery manufacturing workers were significantly associated with odds of blood lead levels (BLLs). [24] A recent study reported high prevalence of pain in limbs, weakness of limbs, and numbness of limbs among these Pb-workers. [25] Also, in severe Pb-poisoning generalized weakness predominates in proximal limbs.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Occupational exposure to lead occurs through inhalation and ingestion. Recent studies on lead-battery manufacturing workers have reported high musculoskeletal disorders with markers of inflammation, 2 mucocutaneous changes, 3 oxidative stress, 4 altered serum magnesium fractions, 5 elevated blood lead levels (BLLs), 6 , 7 reticulocytosis, 8 altered genetic polymorphisms of δ-aminolevulinic acid dehydratase (ALAD), 9 impaired biogenic amino acids with neurobehavioral function, 10 genotoxicity, 11 impaired coagulation function, 12 health problems, 13 , 14 male reproductive function, 15 ocular changes, 16 impaired hematological parameters, 17 and altered calcium metabolism by inhibiting the kidney 1-𝛼-hydroxylase enzyme, which is required for 1, 25 dihydroxy-vitamin D 3 synthesis 18 .…”
Section: Introductionmentioning
confidence: 99%
“…3 , 4 Worker BLLs have been associated with respiratory, gastrointestinal and musculoskeletal morbidities. 5 …”
Section: Introductionmentioning
confidence: 99%